1865-66 N.C. Sess. Laws 103-04, Pub Laws, ch. 40, § 15. - (:unkn) unknown (General Publisher, 1866)
“an act to amend chapter one hundred and seven, section sixty-six, of the Revised Code, relating to free negroes having arms;
--
Keywords: ENSLAVED PERSONS & OTHER MINORITIES